The Role of Digital Transformation in Promoting Digital Entrepreneurship : An Analytical Study of the Opinions of a Sample of Employees in Private Banks in the Middle Euphrates Region - Ali Thamer Abdul Ameer (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The current research aims to identify the role of digital transformation across its dimensions (technology, digitization of operations, databases, human resources) in promoting digital entrepreneurship in its dimensions (digital information base, digital business environment, digital skills and e-leadership, financing) among a sample of employees in private banks in the Middle Euphrates region. The research problem emerged regarding the ability of the private banks under study to use digital transformation and digital entrepreneurship. This problem lies in the lack of environmental stability, limited financial infrastructure, and weak human expertise. Therefore, the research problem was formulated in an important question: What is the impact of digital transformation on promoting digital entrepreneurship in Iraqi private banks? In order to determine the level of research variables, a questionnaire was adopted by distributing (136) questionnaires to employees in private banks in the Middle Euphrates region to measure the nature of the level of the research variables. To analyze the results, the statistical packages (SPSS & AMOS.V.29) were used. As a result, the research produced various results, most notably the existence of a significant correlation between digital transformation and entrepreneurship. Digital businesses contribute to encouraging innovation in developing new financial products and services that meet changing market needs. The results also showed that digital transformation helps private banks improve the efficiency of internal operations, leading to a reduction in transaction time. Furthermore, digital transformation processes can provide smoother and faster financial services, which supports customer satisfaction and loyalty.